Appendicitis as a possible safety signal for the COVID-19 vaccines - Joseph Mitchell; Qun-Ying Yue (Vaccine: X, 2021)
This study reviewed cases of appendicitis following administration of COVID-19 vaccines reported to VigiBase, the WHO database of individual case safety reports (ICSRs). Three hundred fifty-eight cases were identified, and disproportionate reporting was noted, with 329 calculated expected cases. Upon review, 24 ICSRs were excluded, so 334 unique ICSRs underwent clinical review from 19 countries. Forty-eight percent of ICSRs reported imaging and 69% noted surgical intervention. The cases were clinically coherent, with an apparent increase in reporting in the four days post-vaccination and a possible dose–response relationship. Appendicitis has been suggested as an adverse event of special interest post-vaccination against COVID-19 after a numerical increase in the vaccine arm of a clinical trial. The case series may be affected by differences in global patterns of reporting, and it is not possible to prove nor disprove causality from this case series. Global longitudinal studies are required to clarify any possible relationship.